2008
DOI: 10.1051/0004-6361:200809416
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of very powerful FRII radio galaxies

Abstract: Aims. We estimate the ages and physical properties of powerful radio galaxies.Methods. An analysis of new multi-wavelength VLA observations of eleven very powerful classical double (FRIIb) radio galaxies with redshifts between 0.4 and 1.3 is presented. We estimate ages and velocities for each side of each source. The eleven new sources are combined with previously studied samples and the characteristics of the full sample of 31 sources are studied; the full sample includes sources with redshifts between 0.056 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 62 publications
10
117
1
Order By: Relevance
“…The ages of compact radio galaxies are typically estimated as t age = 10 2 -10 3 years (e.g., Orienti et al 2007;Fanti 2009;Giroletti & Polatidis 2009), while the lifetime of extended (up to a few hundred kpc) radio sources are about 10 6 -10 7 years (e.g., Alexander & Leahy 1987;Carilli et al 1991;Fanti et al 1995;O'Dea et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ages of compact radio galaxies are typically estimated as t age = 10 2 -10 3 years (e.g., Orienti et al 2007;Fanti 2009;Giroletti & Polatidis 2009), while the lifetime of extended (up to a few hundred kpc) radio sources are about 10 6 -10 7 years (e.g., Alexander & Leahy 1987;Carilli et al 1991;Fanti et al 1995;O'Dea et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a substantial amount of such compact radio galaxies have been detected and classified with various characteristics: compact symmetric objects (CSO) with a linear scale 1 kpc, gigahertz-peaked spectrum (GPS; 1 kpc) sources, mediumsize symmetric objects (1-10 kpc), and compact steep-spectrum (CSS; 20 kpc) sources (see O'Dea et al 2009). These young radio galaxies (YRGs) are a good laboratory to investigate the physical link between AGN jets and accretion disks.…”
Section: Introductionmentioning
confidence: 99%
“…Deceleration of the flow in the kpc-scale jet has also been examined by several previous investigators [17][18][19][20][21][22] and the flow is found to slow down quickly to near 0.1c beyond a few kpc from the core. As a result radiation from most of the kpc-scale jet must then also be un-boosted.…”
Section: Radiation From the Outer Jet And Giant Radio Lobesmentioning
confidence: 89%
“…When a jetted source contains giant lobes with internal hotspots these features will almost certainly contain most of the source flux. Since outward motion in the lobes has been shown to be close to 0.02c ± 0.01c [15][16][17] the radiation from the lobes will be un-boosted.…”
Section: Radiation From the Outer Jet And Giant Radio Lobesmentioning
confidence: 97%
“…Liu et al 1992;O'Dea et al 2009). Even if we use this boundary, we can explain the source without any misalignment; e.g., if the approaching inner and outer jets are both inclined by φ = 20 • to the line of sight, then a bulk jet speed β inn = 0.9903 would be consistent with the measured Doppler factor in the inner region (Eq.…”
Section: Small-scale Morphologies and Viewing Anglesmentioning
confidence: 99%